Stereotactic body radiotherapy for oligometastatic renal cell carcinoma—are we ready to roll? - Okoye, Christian C.; Patel, Ravi B.; Siva, Shankar; Louie, Alexander V.; Lo, Simon S. (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Approximately 1 in 4 patients with renal cell carcinoma (RCC) present with metastatic disease, with an additional 20–30% experiencing metastatic relapse after primary surgical therapy for localized disease (1). Despite the high rate of local and/or metastatic relapse, there are no randomized studies to guide therapy.